2021
DOI: 10.1021/acs.jpca.1c09106
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the System-Size Dependence of the Local Approximation Error in Coupled-Cluster Calculations

Abstract: Over the last two decades, the local approximation has been successfully used to extend the range of applicability of the “gold standard” singles and doubles coupled-cluster method with perturbative triples CCSD­(T) to systems with hundreds of atoms. The local approximation error grows in absolute value with the increasing system size, i.e., by increasing the number of electron pairs in the system. In this study, we demonstrate that the recently introduced two-point extrapolation scheme for approaching the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 93 publications
(143 reference statements)
1
36
0
Order By: Relevance
“…They showed that this method also decreases the system size dependence of the DLPNO error. 88 We performed two-point extrapolation of the correlation energies, E x and E y , calculated with different T CutPNO thresholds, T CutPNO 1.0 × 10 – x and 1.0 × 10 – y , respectively, according to the following equation: 77 where E ∞ is the correlation energy at the CPS limit and β is a constant. β can be integrated in a parameter F that also depends on the T CutPNO thresholds as follows: and therefore eq 5 can be written as …”
Section: Methodsmentioning
confidence: 99%
“…They showed that this method also decreases the system size dependence of the DLPNO error. 88 We performed two-point extrapolation of the correlation energies, E x and E y , calculated with different T CutPNO thresholds, T CutPNO 1.0 × 10 – x and 1.0 × 10 – y , respectively, according to the following equation: 77 where E ∞ is the correlation energy at the CPS limit and β is a constant. β can be integrated in a parameter F that also depends on the T CutPNO thresholds as follows: and therefore eq 5 can be written as …”
Section: Methodsmentioning
confidence: 99%
“…PM6, ωB97X-D/6-31+G­(d,p), ωB97X-D/6-31++G­(d,p), and DLPNO-CCSD­(T)/aug-cc-pVTZ calculations were employed for the geometry optimization or single-point energy calculations within the multistep sampling scheme. Several studies have shown that the DLPNO-CCSD­(T)/aug-cc-pVTZ//ωB97X-D/6-31++G­(d,p) level of theory shows excellent performance for investigating the Δ G values of atmospheric molecular clusters. The ORCA 4.0.0 program was employed to perform the DLPNO-CCSD­(T)/aug-cc-pVTZ calculation, where tight SCF and PNO convergence criteria were adopted. The other calculations were performed within the Gaussian 09 program .…”
Section: Computational Detailsmentioning
confidence: 99%
“…CPS(6/7) extrapolation has been shown 74 to provide sub-kJ/mol accuracy on the most challenging subsets of the GMTKN55 superset, 30 and it retains essentially canonical CCSD(T) accuracy also for large systems. 131 For the IB8, TA13, and CARB10 sets, the MAE associated with the DLPNO-CCSD(T)/CPS(6/7)/CBS(3/4) results (with respect to the canonical CCSD(T)/CBS benchmark data described above) is only 0.11, 0.08, and 0.04 kcal/mol, respectively. For the TTF-TCNQ pair, the present DLPNO-CCSD(T)/CPS(6/7)/CBS(3/4) interaction energies (see the TTF-TCNQ-DLPNO sheet in the Supporting Information ) were used as the benchmark energies.…”
Section: Computational Detailsmentioning
confidence: 92%